Experimental and numerical studies on CO2 injectivity in low permeability oil reservoirs - Meng, Fankun; Cao, Lin; Zhou, Yuhui; Liu, Botao; Wen, Chengyue; Liu, Jia (Frontiers in Earth Science, 2024)
Contrary to the traditional recognition that CO2 has large injectivity (the ratio of CO2 injection volume to pressure drop) in low permeability oil reservoirs to keep the formation pressure at a high level, the CO2 injection rate usually cannot attain the set value. It is essential to study the factors that influence CO2 injectivity and propose the optimal strategies to improve the CO2 injectivity. Therefore, in this study, several core samples collected from low permeability oil reservoirs are used to experimentally investigate the influences of CO2 injection rate, formation permeability, pressure and water saturation on CO2 injectivity, and the corresponding pressure drop, oil and gas production are examined. To determine the primary factor that influences the CO2 injectivity, orthogonal experimental design (ODE) and numerical simulations are utilized. In addition, to improve CO2 injectivity, the techniques of minifracturing and radial perforation are presented, and the threshold values for these two parameters are determined. The results demonstrate that according to the magnitude of the extent that influences CO2 injectivity, the rank for the above factors is CO2 injection rate, reservoir pressure, formation water saturation and permeability. The oil recovery is mainly influenced by CO2 injection rate and formation permeability, and the influences of reservoir pressure and water saturation on oil recovery are smaller. The threshold values for radial perforation and fracture half-length are 25m and 50m, respectively, which can provide some guidance for the strategies that should be taken to improve the CO2 injectivity and recover more oil from low permeability oil reservoirs.